Jahan, Guliyeva - (:unkn) unknown (My University, 2026)
Jahan Niftali Guliyeva graduated from Ganja State University with a Bachelor’s degree in Economics in 2004 and a Master’s degree with distinction in Economic Theory in 2006. She began her professional career in 2000 as a Laboratory Assistant at Ganja State University. In 2012, she was appointed Tutor at the Department of Master’s and Doctoral Studies of Azerbaijan State Pedagogical University. Since 2019, she has been working at the Azerbaijan University of Architecture and Construction (AzUAC), where she served as a Lecturer at the Department of Economic Theory and Marketing and has been a Senior Lecturer since 2025. Jahan Guliyeva is the author of more than 80 scientific articles, 7 course programmes, and numerous scientific and methodological publications. Her research has been published in Azerbaijan and international journals and conference proceedings.